(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Motivation: It is estimated that every year more than 115 million animals are used for animal experiments worldwide. Following the 3R rules (replace, reduce, refine), researchers are required to find alternatives to animal testing. 3D printing allows for designing models that can replace parts of pre-experiments and in some cases even the animal experiments themselves. Recently, a static rat model was introduced and validated with magnetic particle imaging. In this work, the initial ideas and results will be presented on the way to a dynamic rat phantom. Materials and Methods: The static phantom was designed with a CAD software (Solidworks, Dassault Systems), based on a rat anatomy atlas. The main part of the model was printed with a Form 2 (FormLabs) printer using clear resin. In the model the main organs of the rat are represented (heart, liver, kidney, spleen, lungs and brain). Furthermore, the main vessels like the aorta and vena cava are represented as well as some vessels for the supply of the brain. In order to achieve a successful print, the inner diameter of the vessels had to be adapted to a minimum of 1 mm. Results and Discussion: The main challenge during the construction was the handling of parallel vessels. In contrast to a living animal, the flow resistance of a parallel blood circuit cannot be adapted by the stiffness or width of the vascular system. Thus, the design was changed that the organs are flooded one after the other. Conclusion: As a living organism cannot be completely imitated regardless of the printer accuracy or accurate design, animal experiments will still be necessary. Nevertheless, the presented model can be used to perform initial experiments and experiment planning without using living animals and thus reduces the number of animals necessary for a preclinical trial.